Effects of Program for Blood Pressure Control using Community Participation on Health Behaviors and Blood Pressure in community Dwellers with Hypertension - Thaothong, Naruemon; Piaseu, Noppawan; Maruo, Suchinda Jarupat; Piyatrakul, Sangduen (Journal of Research in Nursing-Midwifery and Health Sciences, 2015)
This Quasi–experimental research aimed to 1) compare health behaviors and blood pressure in an experimental group before and after participating in a program for blood pressure control using community participation, 2) compare health behaviors and blood pressure between a control group and the experimental group after the intervention completion. The sample included 60 persons with hypertension in two communities in Uthaithani Province. The participants were assigned to an experimental group (n = 30) and a control group (n = 30). The experimental group participated in the program for 14 weeks. Data were collected using a health behavior questionnaire for persons with hypertension. The demographic characteristics data were analyzed using descriptive statistics, Chi-square test and Fisher’s exact probability test. Paired t-test and Wilcoxon signed-rank test were used compare health behaviors and blood pressure in the experimental group before and after the intervention. Independent t-test and Mann Whitney U test were used compare health behaviors and blood pressure between the control group and the experimental group after the intervention. Results revealed that the demographic data of the control group and the experimental group were not significantly different. Overall health behaviors in the experimental group, before and after the program, were not significantly different (t = -1.094, p = 0.283), and no significant difference was found from the control group (t = -1.869, p = 0.067). Analysis of the subscales revealed that after the program, the experimental group had significantly higher scores for stress management than before (t = -2.295, p = 0.029) and significantly higher than the control group (Z = -2.013, p = 0.044). Systolic blood pressure was significantly lower than before the program (t = 3.213, p = 0.003) and significantly lower than the control group (t = -2.228, p = 0.030). Diastolic blood pressure was significantly lower than before (t = 4.343, p < 0.001), but not significantly different from the control group (t = -0.492, p = 0.624). The results suggest that nurses and health teams assess and monitor stress and promote activities with community participation, addressing stress management in persons with hypertension, to control blood pressure effectively.